Культурно-освітня складова діяльності кримськотатарської спільноти в Україні - Щерба, О. (Українська національна ідея: реалії та перспективи розвитку, 2011)
Проаналізовано політику Української держави щодо відродження національної
культури, захисту прав і свобод кримськотатарського населення України. Проаналізовано стан культурно-освітнього розвитку кримськотатарської спільноти в Україні. Визначено завдання культурно-освітньої політики України щодо досягнення міжетнічної гармонії та етнокультурної рівноваги в Криму. Запропоновано вирішувати етнокультурні проблеми Криму в межах мультикультуралізму, поважного і позитивного ставлення до різних етнокультурних груп і добровільної орієнтації соціальних інститутів суспільства на їх потреби. The policy of the Ukrainian state in relation to the revival of national culture, defence of rights and freedoms of Crimean tatars population is analysed. Cultural and educational development of Crimean tatars community status in Ukraine is analysed. Task of cultural and educational policy of Ukraine in relation to achievement of interethnic harmony and ethnic-cultural equilibrium in Crimea is shown. To settle the ethnic-cultural problems of Crimea within the limits of multiculturalism, worthy and positive attitude toward different ethnic-cultural groups and voluntarily orientation of social institutes of society on their necessities.